Nanoelectrode for Amperometric Monitoring of Individual Vesicular Exocytosis Inside Single Synapses - Li, Yu-Tao; Zhang, Shu-Hui; Wang, Li; Xiao, Rong-Rong; Liu, Wei; Zhang, Xin-Wei; Zhou, Zhuan; Amatore, Christian; Huang, Wei-Hua (Angewandte Chemie International Edition, 2014)
Chemical neurotransmission occurs at chemical synapses and endocrine glands, but up to now there was no means for direct monitoring of neurotransmitter exocytosis fluxes and their precise kinetics from inside an individual synapse. The fabrication of a novel finite conical nanoelectrode is reported perfectly suited in size and electrochemical properties for probing amperometrically inside what appears to be single synapses and monitoring individual vesicular exocytotic events in real time. This allowed obtaining direct and important physiological evidences which may yield important and new insights into the nature of synaptic communications. Chemical neurotransmission occurs at chemical synapse, but up to now there was no means for direct monitoring of neurotransmitter exocytosis and its precise kinetics from inside individual infinitesimal synapse. A novel finite conical nanoelectrode is fabricated and used in a newly developed amperometric method (see picture) for probing inside what appears to be single synapses.